Pengembangan Rules Driven Workflow Management System Pada Penerimaan Peserta Didik Baru SMK Ketintang Surabaya Untuk Memudahkan Pengelolaan Data Berbasis Website - Pramesti, Shelvi Damayana; Nurcahyawati, Vivine; Ningsih, Norma (Jurnal Sistem Informasi Universitas Dinamika, 2020)
SMK Ketintang Surabaya is one of the private SMK located on Jalan Ketintang 147-151 Surabaya. Every year SMK Ketintang opens registration for prospective new students. The process is carried out with new students or parents of new students coming directly to the SMK and filling out the registration form. The process resulted in the accumulation of registrants, the process of checking prospective students' data and payments tended to be slow, there was a discrepancy of data written in the registration form with those recapitulated by the PPDB committee, archives in physical form that were prone to data loss and damage, the work of the committee piled up causing late confirmation to the principal and the slow process of announcing the admission of new students. The solution that will be made is, an application for developing rules driven workflow management system for new website based student admissions. This application has features such as file checking, recording, reporting, archiving, and announcements to speed up the process of accepting new students. With this application made helps improve the performance of those who handle the registration process. This application also helps in archiving documents that are converted into data. The acceptance of new learners is also easier in managing student data and making reports. The results of the trial application for the development of rules driven workflow management system on the acceptance of new students of the Surabaya-based SMK Ketintang website were able to assist in the management and archiving of new student registration data and the ease of distributing related documents for immediate approval.